Bounded or Boundless: A Case Study of Foreign Correspondents' Use of Twitter During the 2019 Hong Kong Protests. (February 2021) - Luqiu, Luwei Rose; Lu, Shuning
This study advances the understanding of journalists' social media practices by examining the Twitter feeds of foreign correspondents working for Western legacy media during the 2019 Anti-Extradition Law Amendment Bill protests in Hong Kong. We found that these correspondents were more likely to use Twitter to report facts than to express their opinions and that they tended to interact with each other on Twitter far more frequently than with those outside their professional circle. Furthermore, the expression of personal opinions by the correspondents on Twitter appeared to encourage audience engagement. Finally, these personal opinions tended to be sympathetic to the protesters and critical of the handling of the protests by the authorities, especially the police. We argue that news media outlets have a moral obligation to free their journalists from constraints on the exercise of free speech on social media because doing so protects the freedom of the press on both the institutional and individual levels.